Performance of Spirulina Platensis in Oxidation Ditch Reactor for treating To-fu Wastewater - Lolita Kurniasari; Savira Safrilia; Ni Made Maya Febriana Ramadhany; Iqbal Ramadhan; Euis Nurul Hidayah (Nusantara Science and Technology Proceedings)
Spirulina platensis is a type of blue - green algae that has a micro-sized spiral shape and lives in marine waters. There are so many benefits of this microalgae, one of which is it can degrade organic pollutants in wastewater. Excessive nitrate and phosphate in the water can cause eutrophication which is indicated by the death of many sea biotas because of phytoplankton bloom. In this research, tofu which high in organic pollutants are used as experimental test media. The microalgae which will be tested is cultivated first to obtain a sufficient amount for research, then the microalgae are acclimatized before being put into an Oxidation Ditch Reactor mixed with tofu waste with a capacity of 250 liters, ran with 60 rpm brush aerator for 7 x 24 hours and also uses natural lighting from sunlight. samples were taken once a day at 12 noon each day. This research has a variety of wastewater: algae that are 1:1. From the results, it can be observed that Spirulina platensis microalgae could reduce maximum phosphate by 33,15 %, from 18,1 mg/L to 12,1 mg/. Furthermore, microalgae also capable of decreasing nitrates by 46,07 from 0,89 mg/L to 0,48 mg/L.